Functional capacity and treatment data from a community based study of patients with rheumatoid arthritis. Issue 4 (April 1986) - Owen, S G; Friesen, W T; Roberts, M S; Francis, H; Flux, W
Abstract : A community based study of rheumatoid arthritis was undertaken to determine patient characteristics and the patterns of treatment. Three hundred and eighty subjects were visited in their homes throughout Tasmania (pop. 430 000) by a research team. The median age of the sample was 60 years (interquartile range (IR) 49-69), with a female predominance of 2.65 to 1. The average onset age was 41 years (IR 30-53). Prescribing data indicated that polypharmacy was not common in the community, and that the use of slow acting antirheumatic drugs (SAARDs) and oral corticosteroids was not widespread. At the time of the study 26% of subjects were assayed fully functional--class I of the American Rheumatism Association's (ARA) functional classifications. The functional capacity data provided evidence that the spectrum of rheumatoid arthritis found in the community differed from that found in specialist rheumatology clinics.